1977
DOI: 10.1007/bf01869947
|View full text |Cite
|
Sign up to set email alerts
|

Ca ionophore-stimulated ion secretion in rabbit ileal mucosa: Relation to actions of cyclic 3′,5′-AMP and carbamylcholine

Abstract: Addition of the Ca ionophore, A23187 (0.5 gg/ml), to the serosal side of * To whom reprint requests should be addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
83
1

Year Published

1979
1979
2005
2005

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(92 citation statements)
references
References 28 publications
8
83
1
Order By: Relevance
“…Under these conditions prostaglandin action was found to depend on external Ca2+, in contrast with earlier reports (Bolton & Field, 1977) but in agreement with more recent studies (Hardcastle et al 1984). Thus the fact that histamine-induced intestinal secretion was found to require external Ca2+ and was inhibited by the Ca2+-channel blocker verapamil does not rule out its mediation by prostaglandins.…”
Section: Effect Of Histamine On Fluid Transport In Vivosupporting
confidence: 88%
“…Under these conditions prostaglandin action was found to depend on external Ca2+, in contrast with earlier reports (Bolton & Field, 1977) but in agreement with more recent studies (Hardcastle et al 1984). Thus the fact that histamine-induced intestinal secretion was found to require external Ca2+ and was inhibited by the Ca2+-channel blocker verapamil does not rule out its mediation by prostaglandins.…”
Section: Effect Of Histamine On Fluid Transport In Vivosupporting
confidence: 88%
“…These results can also be used to interpret the paradox that choleragen, theophylline and cyclic AMP (Powell, 1974), whilst increasing passive ionic conductance via the paracellular route, also decrease tissue conductance in choleragen and theophylline-induced active secretary state (Field, Fromm, Al-Awqati & Greenough, 1972;Powell et al 1973;Nellans et al 1974;Bolton & Field, 1977). The increase in tissue resistance with theophylline is shown here to occur after an initial decrease in resistance; this decrease is also observed when either, 20 mM-galactose, or triaminopyrimidine is present in the Ringer.…”
Section: Discussionmentioning
confidence: 58%
“…Frizzell, Koch & Schultz (1976) with rabbit colon and Beitch, Beitch & Zadunaisky (1974) with rabbit cornea have shown that cyclic AMP increases active Cl-secretion, short circuit current and also transepithelial conductance in both these 'tight' epithelia. More recently Frizzell (1977) has shown that Ca2+ ionophore A 23187 causes increased short-circuit current due to active Cl-secretion, accompanied by increased electrical conductance across rabbit colon; whereas Bolton & Field (1977) have shown that A 23187 increases short circuit current, and Cl-secretion but decreases transepithelial conductance across rabbit ileum.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the effects of 5-HT on NaCl absorption (10) and Cl Ϫ secretion (42) are mediated by an increase in the intracellular calcium levels. We thus examined the role of calcium in mediating the effects of 5-HT by using the Ca 2ϩ chelator BAPTA-AM (20 M, 1 h).…”
Section: Effect Of Ca 2ϩ Chelator Bapta-am On 5-ht-mediated Inhibitiomentioning
confidence: 99%